Neoadjuvant Savolitinib targeted therapy stage IIIA-N2 primary lung adenocarcinoma harboring MET Exon 14 skipping mutation: A case report - Fu, Meng; Feng, Chun-Mei; Xia, Da-Qing; Ji, Zi-Mei; Xia, Huai-Ling; Hu, Na-Na; Leng, Zai-Jun; Xie, Wang; Fang, Yuan; Cao, Le-Jie; Zhang, Jun-Qiang (Frontiers in Oncology, 2022)
MET exon 14 skipping mutation (METex14m) is rare and occurs in approximately 1-4% of all non-small cell lung cancer (NSCLC) patients and approximately 2.8% of resected stage I-III NSCLC patients. Savolitinib is an oral, potent and highly selective type Ib MET inhibitor, which has been shown to be promising activity and acceptable safety profile in patients with advanced NSCLC harboring METex14m. Most recently, many studies have been probing into the feasibility and efficacy of target therapy for perioperative application in NSCLC. Interestingly, there are very few recorded cases of such treatments. Here, we presented that systemic treatment with the MET inhibitor savolitinib before surgery could provide the potential to prolong overall survival (OS) of patients with locally advanced potentially resectable NSCLC. A 49-year-old woman was diagnosed with stage IIIA (T2bN2M0) primary lung adenocarcinoma exhibiting a METex14m by real-time quantitative polymerase chain reaction (RT-qPCR). Given that the tumor load and the size of lymph nodes experienced a significant downstaging after the neoadjuvant treatment of savolitinib with 600mg once a day for 5 weeks, left lower lobectomy and systemic lymphadenectomy were successfully performed. The pathological response was 50% and the final postoperative pathological staging was pT1cN0M0, IA3 (AJCC, 8th edition). The case provides empirical basis for the neoadjuvant treatment with savolitinib in METex14m-positive locally advanced primary lung adenocarcinoma, which will offer some innovative insights and clinical evidence for more effective clinical treatment of neoadjuvant targeted therapy for METex14m-positive NSCLC.